Assessment of corticospinal tract damage and cytokines response in early and late stages of acute unilateral brainstem infarction patients - Mengye Shi; Huiyou Chen; Xiaojiao Ci; Wen Geng; Xinyang Qi; Yuchen Chen; Xindao Yin (Frontiers in Immunology)
BackgroundAcute brainstem infarction is associated with high morbidity and mortality, the integrity of corticospinal tract (CST) detected via diffusion tensor imaging (DTI) can assist in predicting the motor recovery of the patients. In addition to the damage caused by ischemia and reperfusion, sterile inflammation also contributes to the brain injury after stroke. However, the changes in CST integrity detected by DTI in acute brainstem infarction have yet to be fully elucidated, and it is still unclear whether sterile inflammation can cause damage to the CST.MethodsIn this study, the acute brainstem infarction patients in the early (EABI patients, n = 19) and late (LABI patients, n = 21) stages and healthy controls (HCs, n = 22) are employed. The probabilistic tractography technique was used and the fractional anisotropy (FA) value was chosen to evaluated the integrity of the CST, the IL-6, IL-10, IL-17, IL-1β, and tumor necrosis factor (TNF)-α levels in the plasma are measured to evaluate the level of inflammation.ResultsCompared to the HCs (F = 13.634, p ANOVA < 0.001), the CST FA values on the infarcted side were abnormally elevated in EABI patients (p LSD = 0.003), and decreased in LABI patients (p LSD = 0.034). The levels of IL-6 (F = 12.311, p ANOVA < 0.001, EABI vs HCs: p LSD < 0.001, LABI vs HCs: p LSD < 0.001), IL-10 (F = 11.329, p ANOVA < 0.001, EABI vs HCs: p LSD < 0.001, LABI vs HCs: p LSD = 0.017) and IL-1β (F = 15.986, p ANOVA < 0.001, EABI vs HCs: p LSD < 0.001, LABI vs HCs: p LSD < 0.001) were increased in both EABI and LABI patients, while the IL-17 levels were elevated only in LABI patients (F = 4.258, p ANOVA = 0.019, LABI vs HCs: p LSD = 0.027). Among these cytokines, the increased IL-6 (r = 0.663, p = 0.002) and IL-1β (r = 0.615, p = 0.005) levels of EABI patients might be related to the elevated CST FA values, while the increased IL-17 (r = -0.599, p = 0.004) levels of LABI patients might contribute to the decrease of the CST FA values.ConclusionOur study reveals that the increased CST FA values in EABI patients may include signals generated by the immune cells which move along the CST. The sterile inflammation may contribute to the impairment of CST integrity in LABI patients.